Development of French Language Promotional Content for Cilacap's Leading Tourist Destinations - Dendi Ridho Pramana Yulianto; Neli Purwani (Eduvest - Journal of Universal Studies, 2026)
This study aims to develop French-language promotional content to support the international tourism promotion of Cilacap’s leading tourist destinations. The research addresses the limited availability of foreign-language promotional materials, particularly in French, despite the growing interest of Francophone tourists in Indonesian destinations. A qualitative descriptive method was employed, involving data collection through observation, documentation, and interviews with local tourism stakeholders. The research process included destination analysis, selection of key tourism objects, linguistic adaptation, and content development in French, emphasizing cultural accuracy and persuasive communication. The findings show that well-structured and culturally adapted French promotional texts can enhance destination image, improve accessibility for Francophone tourists, and support local tourism branding strategies. The developed promotional content includes destination descriptions, attractions, facilities, and cultural highlights tailored to French language norms and tourism discourse. This study contributes to tourism communication studies and provides practical implications for local governments and tourism managers in developing multilingual promotional materials to increase international tourist engagement